Disagreeing with Confidence. (23rd October 2017) - Besong, Brian
Abstract: Does having an initially high level of justified confidence in a belief vindicate remaining steadfast in the face of disagreement? According to one prominent view in the literature, namely Jennifer Lackey's justificationist position, the answer is yes so long as one also has personal information that provides a symmetry‐breaker. In this article, I raise a problem for the justificationist view. On the most straightforward reading of the justificationist position, personal information always provides a symmetry‐breaker in a peer dispute over a belief in which one has high justified confidence. However, this position is implausibly strong because it renders epistemically permissible a dogmatic attitude in a relevant set of peer disagreements. Alternatively, weaker readings of the view fail to provide a perspicuous account of when high justified confidence matters in a disagreement.